Revitalisasi Water Level Control Tandon Air Dan Perapihan Tempat Wudhu Yang Rusak Di Mushola Nurul Yaqin Desa Sindang Laut Banten - Sunardi; Aripin Triyanto; Abdul Muchib; Rafael Dinandro Neno; Adelia Syahfitri Hermansyah; Rio Zulfa Adam (CV. Multi Kreasi Media, 2025)
The revitalization of the water level control system and the renovation of the ablution area are strategic efforts to improve the quality of worship facilities at Mushola Nurul Yaqin, Sindang Laut Village, Banten. The previous water control system was inefficient, leading to water wastage and unstable supply, while the damaged ablution area reduced comfort and safety for worshippers. This activity aimed to redesign an automatic water control system using sensors and a microcontroller, as well as to renovate the ablution infrastructure using more durable and functional materials. The implementation results showed that the system could regulate water levels efficiently and in real-time, while the improved ablution facilities provided greater comfort for users. This project has had a positive impact on efficient water management, enhanced worship services, and supports the sustainability of religious facilities within the community.